User-Generated Content: A Systematic Literature Review (SLR) Research - Suryatini, Ni Wayan; Juniman, Puput Tripeni; Riesardhy, Anastasia Winanti; Irwansyah, Irwansyah (JURNAL KOMUNIKASI INDONESIA, 2025)
The advancement of technology has given rise to the phenomenon of user-generated content (UGC), which presents an intriguing subject for investigation through various perspectives. This paper aims to conduct an analysis of journal articles focusing on UGC within the context of the Instagram social media platform. To achieve this, the paper employs a systematic literature review (SLR) research method, adhering to the PRISMA protocol, focusing specifically on journal articles discussing UGC on Instagram. The literature search was conducted in April 2023 using the keywords "UGC" and "Instagram" in the Scopus database. After a series of exclusions, the research examined 30 journal articles relevant to the topic. Eight research questions were addressed based on the conceptual framework, document characteristics, and content dimensions. The analysis results reveal that UGC offers numerous advantages to the communication and marketing industry. These benefits can be realized through the application of specific strategies tailored to the characteristics of Instagram users.